HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN FOREHAND CLEAR DALAM PERMAINAN BULUTANGKIS PADA SISWA EKSTRAKURIKULER DI SD NEGERI 1 BATU GAJAH - Saputra, Niku; Syafutra, Wawan; Fatahilah, Adika (LP4MK STKIP PGRI Lubuklinggau, 2023)
In this case, the researcher wants to know how much arm muscle strength contributes to the accuracy of the Forehand Clear shot. The variables in this study are arm muscle strength as the independent variable (X) and the accuracy of Forehand Clear shots in badminton games as the dependent variable (Y). The method used in this study is the Product Moment Correlation Method and then continued by using the t test to determine the significance of the correlation coefficient. Then, to test how much the contribution of arm muscle strength to the Forehand Clear shot in badminton, the KD (Koefesien Determinasi) test was carried out. Based on the results of research and discussion, it can be concluded that arm muscle strength provides a significant role and relationship to the results of Forehand Clear shots in badminton games for extracurricular students at SD Negeri 1 Batu Gajah with the results of the Hypothesis test where tcount ≥ ttable, (tcount 8.1435 and ttable, 4.4224). In the calculation of the Coefficient of Determination, the KD value = 58.95% is obtained, which means that the contribution of arm muscle strength to the results of the Forehand Clear shot is 58.95%. While 41.05% is the result of the Forehand Clear shot which is influenced by other factors. Keywords: Relationship of Strength, Arm Muscles, Forehand Clear Accuracy